Renal Cell Carcinoma Metastasis to the Breast: A Rare Presentation - Heba O. E. Ali; Tamer Ghorab; Iain R. Cameron; Ahmed M. S. M. Marzouk (Case Reports in Radiology)
Worldwide breast malignancy is the most common cancer in women; however, metastases to the breast from extramammary malignancies are very rare and only a few sporadic cases are reported in the international literature. In this article, the authors report a case of a 73-year-old woman, who underwent nephrectomy for clear cell renal cell carcinoma and 3 years later presented with a breast metastasis from renal cell carcinoma (clear cell type).